SIN^6A + COS^6A= 1-3sin^2
Answers
Answered by
2
Answer:
Step-by-step explanation:
Sin⁶A + Cos⁶A
=> (Sin²A)³ + (Cos²A)³
//We know that a³ + b³ = (a + b)(a²-ab+b²)
=> (Sin²A + Cos²A)(Sin⁴A - Sin²ACos²A + Cos⁴A)
=> Sin⁴A - Sin²ACos²A + Cos⁴A (∵ Sin²A + Cos²A = 1)
=> (Sin²A)² + (Cos²A)² - Sin²ACos²A
//We know that a² + b² = (a + b)² - 2ab
=> (Sin²A + Cos²A)² - 2Sin²ACos²A - Sin²ACos²A
=> 1 - 3Sin²ACos²A
=> R.H.S
Hence proved.
Similar questions
Math,
3 months ago
Chemistry,
3 months ago
English,
7 months ago
Math,
1 year ago
Social Sciences,
1 year ago